Epidemiologia de agravos decorrentes da Tarv em pessoas com HIV/AIDS no município de Altamira/PA - CORREA, Ingrid Dias da Silva (2022)
The epidemiology of the human immunodeficiency syndrome (AIDS) began in the 1980s in the USA with the appearance of diseases considered rare and with an opportunistic character in American homosexuals. Thus, the search for drugs that curb the mechanisms of viral replication, known today as antiretrovirals (ARVs), was crucial, however, the need for their continuous and permanent use can cause adverse effects on the patient that affect their quality of life and full adherence to treatment. OBJECTIVES: To describe the sociodemographic profile, determine the most prevalent comorbidities associated with antiretroviral therapy (ART) and describe possible associations between the use of ART and the emergence of comorbidities in People Living with HIV/AIDS (PLWHA) treated at the CTA in the city of Altamira, Pará. METHODOLOGY: Questionnaires were applied along with a direct interview with the patient, in addition to consulting the medical records present at the site. RESULTS: It was observed that the majority are male (55.77%), single (50.96%), with incomplete elementary and high school education (both with 25.96%), having a monthly family income between 1 at 3 minimum wages (52.88%), taking dolutegravir, lamivudine, tenofovir (52.88%), denying treatment abandonment (60.58%). The percentage of participants who dropped out of treatment was 39.42%. Furthermore, regarding the positive history for other STIs (25.96%), syphilis (7.69%) was highlighted as the most prevalent. Also, the most common acute effects related to the use of ART's, in descending order, were nausea (27.88%), followed by drowsiness (26.92%), diarrhea (22.12%) and headache (18.27 %), and finally, regarding the chronic effects, dyslipidemia (4.81%) stood out. CONCLUSION: The results obtained traced an epidemiological profile of diseases resulting from ART, which provides a scientific basis for the development of better-designed public policies, thus helping in the fight against the advance of HIV and its diseases.